A COMPARATIVE STUDY OF VIDEO LARYNGOSCOPY VS DIRECT LARYNGOSCOPY FOR INTUBATION IN ADULT PATIENTS WITH NON DIFFICULT AIRWAYS SCHEDULED FOR ELECTIVE CHOLECYSTECTOMY - Dr. Preeti Jamwal; Dr. Deepika Jamwal; Dr. Mohinder Singh Chib; Dr. Rajesh Angral; Dr. Sanjay Kalsotra (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Endotracheal intubation is a fundamental procedure in general anesthesia, traditionally performed using direct laryngoscopy. The advent of video laryngoscopy has been associated with improved glottic visualization, increased first-attempt success rates, and potentially fewer complications. Its comparative effectiveness in patients with normal airway anatomy undergoing elective laparoscopic procedures remains an area of clinical interest.Aim: To compare the effectiveness of video laryngoscopy and direct (Macintosh) laryngoscopy in adult patients with normal airway anatomy scheduled for elective laparoscopic cholecystectomy. Methods: This observational study included 90 adult patients (ASA I–II, aged 18–60 years) undergoing elective laparoscopic cholecystectomy under general anesthesia at GMC Kathua. Patients were divided into two groups: Group A (n = 45) underwent intubation using a video laryngoscope, and Group B (n = 45) with a Macintosh laryngoscope. Patients with ASA III or above, anticipated difficult airway (based on Wilson’s score), or age 60 years were excluded. Parameters assessed included time to intubation, number of attempts, Cormack-Lehane grade, and complications such as mucosal trauma and sore throat.Results: Group A (video laryngoscopy) demonstrated a significantly shorter mean intubation time and higher first-attempt success rate compared to Group B. Cormack-Lehane Grade I view was more frequently observed in Group A. The incidence of complications, including mucosal trauma and postoperative sore throat, was lower in the video laryngoscopy group, though not statistically significant.Conclusion: Video laryngoscopy provides improved intubation conditions compared to direct laryngoscopy in adult patients with normal airways undergoing elective laparoscopic cholecystectomy. It offers better glottic visualization, higher first-pass success, and potentially fewer complications, supporting its use in routine practice and as a training tool.